2009
DOI: 10.1103/physrevlett.102.227203
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Momentum-Dependent Exchange Interaction in a Heisenberg Ferromagnet

Abstract: We measured the temperature-dependent three-dimensional angle-resolved photoemission spectra of EuO (100) thin film, a typical Heisenberg ferromagnetic semiconductor, to investigate the essential origin of the ferromagnetic transition. We observed sizable energy dispersion and large binding-energy shift of the Eu 4f state below the Curie temperature only near the Gamma and X points, despite the expected Heisenberg-type local magnetism. The band dispersion and temperature dependence of the Eu 4f state indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 21 publications
8
42
0
Order By: Relevance
“…The splitting between the majority-and minority-spin conduction bands is calculated to be about 0.6 eV, in agreement with previous theoretical studies 26,[32][33][34][35][36] and with recent experiments using three-dimensional (3D) angle-resolved photoemission spectroscopy. 37,38 The Eu-6s states show a spin splitting similar to the Eu-5d states, namely, 0.4 eV.…”
Section: Euo Electronic Structurementioning
confidence: 99%
“…The splitting between the majority-and minority-spin conduction bands is calculated to be about 0.6 eV, in agreement with previous theoretical studies 26,[32][33][34][35][36] and with recent experiments using three-dimensional (3D) angle-resolved photoemission spectroscopy. 37,38 The Eu-6s states show a spin splitting similar to the Eu-5d states, namely, 0.4 eV.…”
Section: Euo Electronic Structurementioning
confidence: 99%
“…In [6], the momentum dependence of exchange coupling is experimentally demonstrated. Our next goal is to choose a specific choice for the momentum dependence, which may produce some impressive results.…”
Section: Conductivity In Ferromagnetic Graphenementioning
confidence: 99%
“…The exchange vector may be a function of coordinate, momentum or time. The authors in [6], have experimentally demonstrated that the exchange coupling in case of the deposition of ferromagnetic insulators may be momentum dependent. On the other hand the spin lens is described in [7] with the help of space dependent exchange field.…”
Section: The Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations